An Investigation of Non-Coplanar Volumetric Modulated Radiation Therapy for Locally Advanced Unresectable Pancreatic Cancer Using a Trajectory Optimization Method - Wang, Gong; Wang, Hao; Zhuang, Hongqing; Yang, Ruijie (Frontiers in Oncology, 2021)
Purpose: To develop a trajectory optimization algorithm for non-coplanar volumetric modulated arc therapy (VMAT), and investigate the potential of organs at risk (OARs) sparing in locally advanced pancreatic cancer patients using non-coplanar VMAT. Methods and materials: Firstly, a cost map that represents the ray-OARs voxel intersections at each source position was generated using a ray-tracing algorithm. A graph search algorithm was then used to determine the least-cost path from the cost map. Lastly, full arcs or partial arcs were selected based on the least-cost path to generate the non-coplanar VMAT (ncVMAT) trajectories. Clinical coplanar VMAT (coVMAT) plans for 11 patients diagnosed with locally advanced unresectable pancreatic cancer (LAPC) receiving 45 to 70 Gy in 25 fractions were replanned using non-coplanar VMAT trajectories. Both coplanar and non-coplanar plans were normalized to cover 95% of the PTV45Gy volume with a prescription dose of 45 Gy. The conformity index (CI), homogeneity index (HI), PTV coverage, and dose to the OARs were compared between coVMAT and ncVMAT plans. Results: With ncVMAT, the mean coverage of PTV50Gy, PTV54Gy, PTV60Gy, and PTV70Gy increased significantly. The mean conformity index of PTV45Gy, PTV54Gy, and PTV70Gy was also improved in the ncVMAT plans. Compared with coVMAT plans, the ncVMAT plans resulted in significantly lower doses to the spinal cord, bilateral kidneys, stomach, and duodenum. The maximum dose to the spinal cord decreased by 6.11%. The mean dose to the left and right kidney decreased by an average of 5.52% and 11.71%, respectively. The Dmax, Dmean, and D15% of the stomach were reduced by an average of 7.45%, 15.82%, and 16.79%, separately. The D15% and Dmean of duodenum decreased 6.38% and 5.64%, respectively. Conclusion: A trajectory optimization algorithm was developed for non-coplanar VMAT. Compared with conventional coplanar VMAT, non-coplanar VMAT resulted in improved coverage and conformity to the targets. The sparing of OARs was significantly improved in non-coplanar VMAT compared with coVMAT plans for locally advanced pancreatic cancer.